ISLAM AND RADICALISM IN SOCIAL LEARNING THEORY PERSPECTIVE - Sri Rejeki (Pascasarjana Universitas Wahid hasyim Semarang, 2013)
Islam and radicalism are two very different things. It is then unjustified to emerge the term